Energy-Efficient Design of Immigrant Resettlement Housing in Qinghai: Solar Energy Utilization, Sunspace Temperature Control, and Envelope Optimization - Bo Liu; Yu Liu; Qianlong Xin; Xiaomei Kou; Jie Song (Buildings)
Qinghai Province urgently requires the development of adaptive energy-efficient rural housing construction to address resettlement needs arising from hydropower projects, given the region’s characteristic combination of high solar irradiance resources and severe cold climate conditions. This research establishes localized retrofit strategies through systematic field investigations and Rhinoceros modeling simulations of five representative rural residences across four villages. The key findings reveal that comprehensive building envelope retrofits achieve an 80% reduction in energy consumption. South-facing sunspaces demonstrate effective thermal buffering capacity, though their spatial depth exhibits negligible correlation with heating energy requirements. An optimized hybrid shading system combining roof overhangs and vertical louvers demonstrates critical efficacy in summer overheating mitigation, with vertical louvers demonstrating superior thermal and luminous regulation precision. Architectural orientation analysis identifies an optimal alignment within ±10° of true south, emphasizing the functional zoning principle of positioning primary living spaces in south-oriented ground floor areas while locating auxiliary functions in northeastern/northwestern zones. The integrated design framework synergizes three core components: passive solar optimization, climate-responsive shading mechanisms, and performance-enhanced envelope systems, achieving simultaneous improvements in energy efficiency and thermal comfort within resettlement housing constraints. This methodology establishes a replicable paradigm for climate-resilient rural architecture in high-altitude, solar-intensive cold regions, effectively reconciling community reconstruction needs with low-carbon development imperatives through context-specific technical solutions.